ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT DI MTS. MUHAMMADIYAH CURUP UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN AQIDAH AKHLAK - Reni Dianti Rukmini; Abdul Rahman; Muhammad Idris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the use of power point learning media in increasingstudents' interest in learning the subject of aqidah akhlak in MTs. The researchmethod used is a descriptive qualitative approach with data collection techniquesthrough observation, interviews, and documentation. The subjects of this studywere teachers of the subject of aqidah akhlak and students of grades VII, VIII andIX MTs. Muhammadiyah Curup. Data analysis was carried out with the steps ofdata reduction, data presentation, and drawing conclusions. The results of thestudy indicate that the use of power point media in learning aqidah akhlak canincrease students interest in learning. This can be seen from the increase in activestudent participation, enthusiasm in participating in learning, and ease inunderstanding the material. Teachers also expressed that the use of power pointmedia helps deliver material in a more structured and interesting way.